PENGARUH TATAKELOLA, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI - Doli Santomans Manurung; Arles Ompusunggu; Estralita Trisnawati (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This study aims to examine the effect of independent commissioners, managerial ownership, leverage, firm size and the effect of independent commissioners moderated by sales growth, managerial ownership moderated by sales growth, leverage moderated by sales growth and firm size moderated by sales growth on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. This study uses purposive samping and elect 73 manufacturing companies as samples in the study and used multiple linear regression analysis using spss.25.00. The results in this study indicate that independent commissioners and leverage have a positive and significant effect on earnings management, managerial ownership have a negative and significant effect on earnings management and firm size has no effect on earnings, sales growth cannot moderate the effect of independent, managerial ownership, leverage, firm size on earnings management